2022
DOI: 10.3389/fneur.2022.844674
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Fast Discharges Along the Genetic Generalized Epilepsy Spectrum: Clinical and Prognostic Significance

Abstract: ObjectiveTo investigate the electroclinical characteristics and the prognostic impact of generalized fast discharges in a large cohort of genetic generalized epilepsy (GGE) patients studied with 24-h prolonged ambulatory electroencephalography (paEEG).MethodsThis retrospective multicenter cohort study included 202 GGE patients. The occurrence of generalized paroxysmal fast activity (GPFA) and generalized polyspike train (GPT) was reviewed. GGE patients were classified as having idiopathic generalized epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Three studies confirmed the prognostic value of generalized polyspike trains (GPTs)—a feature usually associated with LGS, which was first described by Sun et al in a cohort of patients referred for long‐term EEG monitoring, and confirmed by Cerulli Irelli et al and Kamitaki et al 41 , 42 , 43 Conrad et al complemented these studies by showing that GPTs were twice as often found in sleep than in wake EEGs, stressing the need for prolonged EEG recordings (>24 h) to capture GPTs, which is in keeping with findings by Jensen et al, showing that GPTs are rare on routine EEGs. 44 …”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Three studies confirmed the prognostic value of generalized polyspike trains (GPTs)—a feature usually associated with LGS, which was first described by Sun et al in a cohort of patients referred for long‐term EEG monitoring, and confirmed by Cerulli Irelli et al and Kamitaki et al 41 , 42 , 43 Conrad et al complemented these studies by showing that GPTs were twice as often found in sleep than in wake EEGs, stressing the need for prolonged EEG recordings (>24 h) to capture GPTs, which is in keeping with findings by Jensen et al, showing that GPTs are rare on routine EEGs. 44 …”
Section: Resultsmentioning
confidence: 76%
“…Generalized paroxysmal fast activity (GPFA) is traditionally linked to LGS but is seen in 5.6%–18.9% of patients with otherwise typical IGE with absence seizures 46,47 . In several large independent cohorts, GPFA has been linked to persistent seizures and drug resistance in both children and adults 42,47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPFA was historically considered a marker for Lennox-Gastaut syndrome or other epileptic encephalopathies ( 19 – 21 ). More recently, this was recognized in patients with normal cognition and generalized epilepsy ( 22 25 ). Most recent studies have described the association between the presence of GPFA and drug resistance and no specific association with a particular type of generalized epilepsy ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 95%
“…More recently, this was recognized in patients with normal cognition and generalized epilepsy ( 22 25 ). Most recent studies have described the association between the presence of GPFA and drug resistance and no specific association with a particular type of generalized epilepsy ( 25 , 26 ). Focal PFA has also been described in patients with focal epilepsy, and their relationship to seizure onset zone and intractability has been suggested ( 27 29 ).…”
Section: Introductionmentioning
confidence: 95%